Resolving Interpersonal Conflicts through Accessible Justice in Rwanda: The Contribution of Access to Justice Bureaus - John, Gasasira; Gachihi, Margaret; Amatsimbi, Herbert; Ruvebana, Etienne (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
This article examines the contribution of accessible justice to conflict resolution and its translation into sustainable peace. It adopts a case study of Access to Justice Bureaus- a judicial service established by the Government of Rwanda to help people access free legal remedies. Subsequently, the study investigates how far granting people access to justice helps in resolving conflicts between members of the community.While most of the work on justice in post-conflict settings addresses justice for crimes tied to mass violence, this study charts a new territory and broadly looks at how peace is built through the accessibility of justice for crimes not tied to mass violence. Based on the experiences and perceptions of 40 individual interviews and 5 focus group discussions, findings show that there is a significant relationship between the accessibility of judicial services and a peaceful relationship between members of society. In this study, the legalservices provided ensured respect for the rule of law, conflict mediation, and restoration of social bonds between members of the society.